Predictors of spontaneous resolution of umbilical hernia in children - Ahmed Nasr; Manvinder Kaur; Viviane Grandpierre; Irina Oltean; Arielle Weir (BMJ Publishing Group, 2021)
Objective The aims were to describe the management of umbilical hernias, to define postoperative complications, and to identify the characteristics of patients that were more likely to have spontaneous resolution of their hernia.Methods All patients referred for umbilical hernia at the Children's Hospital of Eastern Ontario from January 1990 to April 2017 were examined via retrospective chart review. Spontaneous resolution of umbilical hernia was examined using binary logistic regression.Results We included 2621 patients presenting with an umbilical hernia. A total of 1587 (60.5%) patients underwent surgical repair at a median age of 3.6 years (IQR 2.3-5.4). Surgical complications consisted of infection (n=3), bleeding (n=3), hematoma (n=3), and anesthesia-related complications (n=3). For every one-unit increase in defect size, the odds of a spontaneous resolution of the hernia were 5% lower while controlling for prematurity and the presence of comorbidities [adjusted odds ratio (aOR)=0.95; 95% confidence intervel (CI) 0.93 to 0.97]. Premature babies were 80% less likely to experience hernia resolution compared with non-premature babies (aOR=0.20; 95% CI 0.03 to 0.74).Conclusion The odds of spontaneous resolution were lower for premature babies and were negatively correlated with defect size.